Economies of Scale and Merger Efficiencies: Empirical Evidence from the Chilean Pension Funds Market - Agostini, Claudio; Saavedra, Eduardo; Willington, Manuel (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2012)
Over the last twenty years there has been a deep concentration process in the Pension Fund Manager (AFPs) industry in Chile (from 21 firms in 1994 to only 6 in 2012). A major concern with the concentration of this industry is that firms might be able to exercise market power. However, significant efficiency gains could result from this concentration process, especially if there are economies of scale present in the industry. The welfare effect of a merger is, therefore, ambiguous. In this paper we estimate the welfare implications of a merger between two medium-sized AFPs in Chile. For this purpose, we estimate the size of the economies of scale in this industry and use the results to simulate the merger using a simple imperfect competition model. The estimations, based on quarterly financial information for the last 8 years of the Chilean Pension Funds system, show robustly the presence of significant economies of scale in operating costs. The merger simulation indicates that despite the cost savings, the merger would induce a small price increase. This effect reduces consumer welfare, but aggregate welfare increases because of the efficiency gains from the economies of scale. Since aggregate elasticity in this industry is zero (because affiliation is compulsory), the price increase does not generate any efficiency loss.
Keywords: Mergers; Economies of Scale; Merger Simulation Models; Pension Funds